The Relationship Between Prediabetes and Bone Mass in Adolescents: Analysis of the National Health and Nutrition Examination Survey From 2005 to 2010 - Ma, Chun-Ming; Yin, Fu-Zai (Frontiers in Endocrinology, 2021)
Objective The purpose of this study was to observe the relationship between impaired fasting glucose (IFG), impaired glucose tolerance (IGT), and bone mineral density (BMD) in different sites in adolescents. Methods A retrospective study was conducted on adolescents age 12–19 years of the United States. Data were extracted from the National Health and Nutrition Examination Survey (NHANES) 2005–2006, 2007–2008, and 2009–2010 cycles. IFG was defined as fasting plasma glucose (FPG) levels that were ≥5.6 and <7.0 mmol/L. IGT was defined as 2-h plasma glucose levels that were ≥7.8 and <11.1 mmol/L after the oral glucose tolerance test (OGTT). Results After controlling for age, gender, race, and body mass index (BMI) Z-score, adolescents in different categories of IGT had significantly different levels of areal BMD (aBMD) and bone mineral apparent density (BMAD) (IGT main effect: P < 0.05 for all, two-way ANOVA). There was no main effect between different categories of IFG with regard to aBMD and BMAD (P > 0.05). There was no interaction between IFG and IGT with regard to aBMD and BMAD (P > 0.05). In multiple regression analysis, the 2-h plasma glucose maintained an independent association with femoral neck aBMD (β = −0.011, 95% CI: −0.017~−0.006, P < 0.001, R2 = 0.012), total femur aBMD (β = −0.015, 95% CI: −0.021~−0.009, P < 0.001, R2 = 0.018), total spine aBMD (β = −0.015, 95% CI: −0.020~−0.010, P < 0.001, R2 = 0.018), and total spine BMAD (β = −0.002, 95% CI: −0.003~0.000, P = 0.006, R2 = 0.003). Conclusion The present study demonstrates that BMD was decreased in adolescents with IGT. Two-hour plasma glucose, not FPG, negatively correlated with BMD. The effect of 2-h plasma glucose was consistent across the sites of bone.